Peningkatan prestasi belajar PJOK pada siswa kelas 4 SDN 01 Sengare menggunakan media e-modul di masa pandemi - Aslori Lukman (Action Research Journal, 2021)
The aim of the researcher is to apply e-module media to improve PJOK learning achievement in 4th grade students of SDN 01 Sengare. This research was conducted on 4th grade students of SDN 01 Sengare, Pekalongan Regency with an odd semester of the 2020/2021 academic year, totaling 22 students. This type of research is classroom action research (CAR). As a form of CAR, this research was carried out in several cycles. The results of the study focused on the students' ability to solve problems. The flow in classroom action research begins with planning action (planning), implementing action (action), observing and evaluating the process and results of the action, and reflecting, and so on until the improvement or improvement is expected (success criteria). The result of this research is an increase in the average of students in cycle 1 and cycle 2 respectively 79.50 and 88.25. Then for classical completeness in cycle 1 and cycle 2, respectively 77.27% and 86.36%. Because it has met the predetermined success indicators, there is no need to proceed to the next cycle.